A rare case of prostatic ductal adenocarcinoma presenting as papillary metastatic carcinoma of unknown primary: A case report and review of the literature - Erik R. Washburn, MD; Grace W. Weyant, MD; Ximing J. Yang, MD, PhD; Zhaohai Yang, MD, PhD (Elsevier, 2016)
Prostatic ductal adenocarcinoma is an uncommon form of prostatic carcinoma. We report a case of a 63-year-old man who presented with non-infective thrombotic (marantic) endocarditis and an incidental finding of a destructive lesion in the left iliac crest. Core biopsy of the lesion showed a carcinoma with papillary architecture and was initially diagnosed as "metastatic carcinoma of unknown origin". The patient experienced a cerebral infarction and expired six days later. Postmortem examination revealed extensive mixed acinar and ductal adenocarcinoma (Gleason score 5 + 4 = 9) in the prostate. Further studies confirmed the bone lesion as metastatic prostatic ductal adenocarcinoma. Although rare, metastatic prostatic adenocarcinoma should be considered in the differential diagnosis in a male patient when the carcinoma shows predominantly papillary architectures. A review of literature is presented to enhance the awareness of this entity.